2018
DOI: 10.18632/aging.101614
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of glycogen synthase kinase-3α is required for mitochondria-mediated apoptotic germ cell phagocytosis in Sertoli cells

Abstract: The rapid and efficient clearance of apoptotic germ cells (GCs) by Sertoli cells (SCs) is important for spermatogenesis. High mitochondrial activity in phagocytes is critical for continued clearance of apoptotic cells. However, the underlying molecular mechanism is poorly understood. Glycogen synthase kinase-3α (GSK3α) is a protein kinase that participates in the regulation of mitochondrial activity. Immunohistochemistry evidenced the predominant presence of the Ser21 phosphorylation GSK3α (inactivation) signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…We and others have reported that the mitochondrial membrane potential is a key determinant of apoptotic cell clearance in Sertoli cells (Park et al, 2011; Gong et al, 2018). In the present study, corticosterone resulted in decreased mitochondrial membrane potential in Sertoli cells.…”
Section: Discussionmentioning
confidence: 83%
“…We and others have reported that the mitochondrial membrane potential is a key determinant of apoptotic cell clearance in Sertoli cells (Park et al, 2011; Gong et al, 2018). In the present study, corticosterone resulted in decreased mitochondrial membrane potential in Sertoli cells.…”
Section: Discussionmentioning
confidence: 83%
“…Apparently, this efflux mechanism maintains the intracellular levels of this species relatively stable, even if increased (Figure 1D), during the response to Cd toxicity. These findings highlight the phagocyte-like properties of these cells upon stimulation of stress pathways by the exposure to either xenobiotics and oxidative stress, 27,[46][47][48] as well as to physiological stimuli, such as during ectoplasmic specialization to support all phases of germ cell development and maturity. 49,50 MLT co-treatment significantly prevented the effects of Cd on cell viability and abnormal ROS production (Figure 1C,D), confirming the cytoprotective function and antioxidant properties of this hormonal substance 20 and its relevance in preventing Cd toxicity.…”
Section: Effect Of CD and Mlt On Porcine Scs Viability And Ros Produc...mentioning
confidence: 81%
“…Previous studies revealed that activation of the phosphoinositide 3 kinase (PI3K)/Akt signaling pathway enhances the mitochondrial membrane potential and inhibits the production of reactive oxygen species, leading to regulate cellular processes and memory deficits [27, 28]. PI3K can activate downstream kinase Akt through phosphorylation at the ser473 residue and subsequently leading to phosphorylation of its downstream substrate GSK3β at ser9 residue, thus inhibits the activity of GSK3β [29]. In addition, Bcl-2, and cleaved-caspase-3 are important mediators of AD that are relevant to the regulation of mitochondrial apoptosis as the downstream targets of Akt [30, 31].…”
Section: Discussionmentioning
confidence: 99%